Occlusal wear in humans: anthropological perspective - Cucina, Andrea (2024)
Occlusal wear has been present in humans since the beginning of our evolutionary journey. Even considering its intrinsic limitations, its study is central to estimating age at death, making inferences on diet, on the way food was prepared, and on cultural non-masticatory use of teeth. Its study allows us to understand how occlusal wear has responded to the evolutionary changes that characterized human beings from the onset of agriculture up to the more recent Industrial Revolution. This brief review paper focuses on the study of occlusal wear from an anthropological and bioarchaeological perspective. It discusses its importance for understanding past societies, its advantages, and its limitations in anthropological studies of skeletonized individuals, and how different fields of study in odontology, dental anthropology/bioarchaeology focus on occlusal wear from very distinctive and rarely overlapping perspectives, but that can significantly benefit from one another in a multidisciplinary approach.